Effect of surface chemistry of Fe-Ni nanoparticles on mechanistic pathways of azo dye degradation - Bokare, Alok D.; Chikate, Rajeev C.; Rode, Chandrashekhar V.; Paknikar, Kishore M. (Environmental Science & Technology, 2007)
The degradation of Orange G a monoazo dye, in aqueous solutions was investigated using as-synthesized and stored Fe-Ni bimetallic nanoparticles. Batch experiments with a nanocatalyst loading of 3 g/L showed complete. dye degradation (150 mg/L) after 10 min of reactiontime. HPLC-MS analysis of the degradation products showed that assynthesized nanoparticles reductively cleaved the azo linkage to produce aniline as the major degradation product. However, 1-year-stored nanoparticles showed an oxidative degradation of Orange G through a hydroxyl-radical induced coupling of parent and/or product molecules. XPS analysis in corroboration with HPLC-MS data showed that the surface chemistry between Fe and Ni in assynthesized and stored nanoparticles play a crucial role. in directing the mode of degradation. Reductive dye degradation using as-synthesized nanoparticles proceeded through hydride transfer from nickel, whereas formation of a Fe (2+) -Ni(0) galvanic cell in stored nanoparticles generated hydroxyl radicals from water in a nonFenton type reaction. The latter were responsible for the generation of radical centers on the dye molecule, which led to a coupling-mediated oxidative degradation of Orange G. The generation of hydroxyl radicals is further substantiated with radical quenching experiments using ascorbic acid indicating that stored nanoparticles degrade Orange G through a predominantly oxidative mechanism. HPLC-MS and XPS analysis of dye degradation using as-synthesized nanoparticles exposed to air and water confirmed that the reductive or oxidative degradation capability of Fe-Ni nanoparticles is decided by the time and type of catalyst aging process.

Phosphotungstic acid as an efficient solid catalyst for intramolecular rearrangement of benzyl phenyl ether to 2-benzyl phenol - Bhure, Mahesh H.; Rode, Chandrashekhar V.; Chikate, Rajeev C.; Patwardhan, Neeraj; Patil, Shraddha (Catalysis Communications, 2007)
An heteropoly acid (phosphotungstic acid, PTA) was found to be a promising solid acid catalyst as an alternative to the conventional stoichiometric reagents for the rearrangement of benzyl phenyl ether giving 2-benzyl phenol as a major product and 4-benzyl phenol and dibenzylated phenols as side products. Catalyst was recovered from the reaction mixture and reused again without loss of activity. Based on the observed product distribution for various substrates a plausible catalytic reaction pathway has also been proposed. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: benzyl phenyl ether; Intramolecular rearrangement; Phosphotungstic acid

Iron-nickel bimetallic nanoparticles for reductive degradation of azo dye orange G in aqueous solution - Bokare, Alok D.; Chikate, Rajeev C.; Rode, Chandrashekhar V.; Paknikar, Kishore M. (Applied Catalysis B-Environmental, 2008)
The degradation of Orange G, a monoazo dye, in aqueous solutions was investigated using Fe-Ni bimetallic nanoparticles. Transmission electron microscopy (TEM) of as-synthesized nanoparticles showed the presence of spherical particles having a size of 20-40 nm. X-ray photoelectron spectroscopy (XPS) did not detect the presence of nickel on the nanoparticle surface, which suggested a uniform distribution of both metals inside the particle core. Batch experiments with a minimum nanocatalyst loading of 3 g/L showed complete dye degradation after 10 min of reaction time. The degradation efficiency was linearly dependent on the initial dye concentration, pH of the solution and total Fe-Ni catalyst concentration. The efficiency increased with increasing Fe-Ni concentration and decreasing pH of the solution, but decreased with an increase in the dye concentration. The degradation rate followed first order reaction kinetics with respect to the dye concentration. High performance liquid chromatography-mass spectrometry (HPLC-MS) analysis of the degradation products revealed that the degradation mechanism proceeds through a reductive cleavage of the azo linkage resulting in the formation of aniline and surface-adsorbed naphthol amine derivatives. The latter are subsequently hydroxylated through an oxidative process. (C) 2007 Elsevier B.V. All rights reserved.
Keywords: Azo Dye; Degradation; iron; Nanoparticles; Nickel

Nonaqueous synthesis and characterization of capped alpha-Fe2O3 nanoparticles from iron(III) hydroxy-oleate precursor - Chikate, Rajeev C.; Jun, Ki-Won; Rode, Chandrasekhar V. (Polyhedron, 2008)
The synthesis of capped alpha-Fe2O3 nanoparticles from thermal treatment of iron (III) hydroxy-oleate in boiling organic solvents around 250 degrees C with retention of the integrity of the oleate units during the reaction process is reported. The formation of capped iron oxide particles is accomplished under aerobic conditions while the solvents used in the synthesis have strong influence on the nature and morphology of nanoparticles. These nanoparticles are studied by means of X-ray powder diffraction, IR and XPS while the morphology and particle size of nanocrystals are evaluated using SEM and TEM analysis suggesting the formation of monocrystalline alpha-Fe2O3 particles having cubical and spherical morphologies with sizes ranging from 20 to 30 nm. This organophilic material with oleate capping around the surfaces can be readily dispersed in organic solvents thus forming organosols. These organosols exhibit band-edge emission photoluminescence band both in toluene as well as in solid state while FT-IR analysis reveals formation oleate capped nanoparticles The XPS data indicate ferric state having doublet from Fe 2P(3/2) and Fe 2p(1/2) core-level electrons. (c) 2007 Elsevier Ltd. All rights reserved.
Keywords: alpha-Fe2O3; capped nanoparticles; cubic morphology; ferrofluids; nonaqueous synthesis; Oleic acid; organosol

Phosphotungstic acid on silica with modified acid sites as a solid catalyst for selective cleavage of tert-butyldimethylsilyl ethers - Bhure, Mahesh H.; Kumar, Indresh; Natu, Arun D.; Chikate, Rajeev C.; Rode, Chandrashekhar V. (Catalysis Communications, 2008)
The strength and nature of acid sites of bulk phosphotungstic acid could be modified after dispersing it on silica support which was characterized by XRD, ammonia TPD and (31)P MAS NMR techniques. This solid acid catalyst was found to be highly selective for the cleavage of tert-butyldimethylsilyl ethers at room temperature. The catalyst was easily recovered by filtration and could be reused for several times without loss of any activity giving a TON of 9.5 x 10(5). (C) 2008 Elsevier B.V. All rights reserved.
Keywords: Ammonia TPD; Catalytic cleavage; reaction pathway; solid acid; tert-butyldimethylsilyl ethers; XRD

Solid acid catalysts: modification of acid sites and effect on activity and selectivity tuning in various reactions - Rode, C. V.; Garade, Ajit C.; Chikate, Rajeev C. (Catalysis Surveys from Asia, 2009)
The effects of acidity and variation in concentration of acid sites of dodecatungstophosphoric acid (DTP), supported DTP and montmorillonite-K catalysts were studied for various organic reactions such as the hydroxyalkylation of phenols to bisphenols, intramolecular rearrangement of benzyl phenyl ether (BPE) to 2-benzyl phenol (2-BP) and selective cleavage of tert-butyldimethylsilyl (TBDMS) ether into the corresponding alcohol. Both dodecatungstophosphoric acid (DTP) impregnated on silica (SiO(2)) and montmorillonite catalysts showed the highest catalyst activity with 90-95% selectivity to bisphenol for the hydroxyalkylation of phenols to give bisphenol. Temperature Programmed Desorption (TPD) of ammonia and activity results of various catalysts showed that an appropriate combination of both strong and weak acidic sites in the catalyst was highly desirable for high bisphenol selectivity. A 10% DTP/SiO(2) catalyst was found to be highly selective for the cleavage of TBDMS ether into the corresponding alcohol at room temperature giving a high TON of 9.5 x 10(5) even after the 4th recycle. DTP was also found to be a promising solid acid catalyst for the intramolecular rearrangement of BPE giving 2-BP.
Keywords: Acidity tuning; Catalytic cleavage; Hydroxyalkylation; Intramolecular rearrangement; solid acid catalysts

Reductive dechlorination of gamma-hexachlorocyclohexane using Fe-Pd bimetallic nanoparticles - Nagpal, Varima; Bokare, Alok D.; Chikate, Rajeev C.; Rode, Chandrashekhar V.; Paknikar, Kishore M. (Journal of Hazardous Materials, 2010)
Nanoscale Fe-Pd bimetallic particles were synthesized and used for degradation of lindane (gamma-hexachlorocyclohexane) in aqueous solution. Batch studies showed that 5 mg/Lof lindane was completely dechlorinated within 5 min at a catalyst loading of 0.5 g/L and the degradation process followed first-order kinetics. GC-MS analysis in corroboration with GC-ECD results showed the presence of cyclohexane as the final degradation product. The proposed mechanism for the reductive dechlorination of lindane involves Fe corrosion-induced hydrogen atom transfer from the Pd Surface. The enhanced degradation efficiency of Fe-Pd nanoparticles is attributed to: (1) high specific surface area of the nanoscale metal particles (60 m(2)/g), manyfold greater that of commercial grade micro- or milli-scale iron particles (similar to 1.6 m(2)/g); and, (2) increased catalytic reactivity due to the presence of I'd on the Surface. Recycling and column studies showed that these nanoparticles exhibit efficient and sustained catalytic activity. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: Bimetallic; Cyclohexane; Degradation; kinetics; Lindane; Nanoparticles

Efficiency and recycling capability of montmorillonite supported Fe-Ni bimetallic nanocomposites towards hexavalent chromium remediation - Kadu, Brijesh S.; Sathe, Yogesh D.; Ingle, Abhijit B.; Chikate, Rajeev C.; Patil, Kashinath R.; Rode, Chandrashekhar V. (Applied Catalysis B-Environmental, 2011)
The remediation of Cr(VI) from simulated water streams is investigated using Fe-Ni bimetallic nanoparticles (Fe-Ni NPs) and their nanocomposites prepared with montmorillonite (MMT) clay. These nanocomposites are characterized using X-ray diffraction (XRD), transmission electron microscopy (TEM), X-ray photoelectron spectroscopy (XPS) and Brunauer-Emmett-Teller (BET) surface area analyses. XRD analysis revealed proper dispersion as well as intercalation of Fe-Ni NPs in the clay matrix. TEM of nanocomposites showed the presence of spherical particles having a size of 20-40 nm. Batch experiments with a 25 mg L(-1) Cr(VI) solution and 2 g L-1 Fe-Ni NPs exhibited complete reduction of Cr(VI) within 10 min that follows first order reaction kinetics. Amongst 25%, 50%, 75% in situ and loaded nanocomposites, 75% compositions possess better activity with enhanced reduction capacity below pH 4 due to generation of reactive H center dot species. XPS analysis of nanocomposites after Cr(VI) treatment suggested that reduction process occurs through Cr(111) formation followed by its subsequent reduction to Cr(0). Their potentiality towards reusage is established from the recycling experiments that revealed the order of efficiency as 75% in situ > Fe-Ni NPs > 75% loaded nanocomposites. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: Cr(VI) remediation; Iron-nickel bimetallics; Montmorillonite; Nanocomposites; Recycling

Reply to comment on ``Reductive dechlorination of gamma-hexachlorocyclohexane using Fe-Pd bimetallic nanoparticles'', by C. Noubactep - Nagpal, Varima; Bokare, Alok D.; Chikate, Rajeev C.; Rode, Chandrashekhar V.; Paknikar, Kishore M. (Journal of Hazardous Materials, 2012)

Synthesis, characterization and in vitro study of biocompatible cinnamaldehyde functionalized magnetite nanoparticles (CPGF Nps) for hyperthermia and drug delivery applications in breast cancer - Wani, Kirtee D.; Kadu, Brijesh S.; Mansara, Prakash; Gupta, Preeti; Deore, Avinash V.; Chikate, Rajeev C.; Poddar, Pankaj; Dhole, Sanjay D.; Kaul-Ghanekar, Ruchika (Plos One, 2014)
Cinnamaldehyde, the bioactive component of the spice cinnamon, and its derivatives have been shown to possess anticancer activity against various cancer cell lines. However, its hydrophobic nature invites attention for efficient drug delivery systems that would enhance the bioavailability of cinnamaldehyde without affecting its bioactivity. Here, we report the synthesis of stable aqueous suspension of cinnamaldehyde tagged Fe3O4 nanoparticles capped with glycine and pluronic polymer (CPGF NPs) for their potential application in drug delivery and hyperthermia in breast cancer. The monodispersed superparamagnetic NPs had an average particulate size of similar to 20 nm. TGA data revealed the drug payload of similar to 18%. Compared to the free cinnamaldehyde, CPGF NPs reduced the viability of breast cancer cell lines, MCF7 and MDAMB231, at lower doses of cinnamaldehyde suggesting its increased bioavailability and in turn its therapeutic efficacy in the cells. Interestingly, the NPs were non-toxic to the non-cancerous HEK293 and MCF10A cell lines compared to the free cinnamaldehyde. The novelty of CPGF nanoparticulate system was that it could induce cytotoxicity in both ER/PRpositive/Her2 negative (MCF7) and ER/PRnegative/Her2 negative (MDAMB231) breast cancer cells, the latter being insensitive to most of the chemotherapeutic drugs. The NPs decreased the growth of the breast cancer cells in a dose-dependent manner and altered their migration through reduction in MMP-2 expression. CPGF NPs also decreased the expression of VEGF, an important oncomarker of tumor angiogenesis. They induced apoptosis in breast cancer cells through loss of mitochondrial membrane potential and activation of caspase-3. Interestingly, upon exposure to the radiofrequency waves, the NPs heated up to 41.6 degrees C within 1 min, suggesting their promise as a magnetic hyperthermia agent. All these findings indicate that CPGF NPs prove to be potential nano-chemotherapeutic agents in breast cancer.

Reductive cyclization of levulinic acid to gamma-valerolactone over non-noble bimetallic nanocomposite - Kadu, Brijesh S.; Hengne, Amol M.; Biradar, Narayan S.; Rode, Chandrashekhar V.; Chikate, Rajeev C. (Industrial & Engineering Chemistry Research, 2016)
Bimetallic nanoparticles have diverse applications in catalytic processes owing to the differences in individual properties that contribute to their increased catalytic activity. To further improve the efficiency, they are dispersed in an inert support that enhances the catalytic activity toward organic transformations. In this study, we report simple, facile, and cost-effective chemical route for the fabrication of nanocomposites with Fe-Ni bimetallic nanoparticles supported on montmorillonite (MMT) possessing variation in the Fe and Ni content. These composites are characterized with X-ray diffraction, transmission electron microscopy surface area, and NH3-TPD. Fe Ni bimetallic nanoparticles are well-dispersed within MMT structure having particle sizes of about 30-40 nm. Among various compositions of Fe-Ni/MMT catalysts, composite with 25% Fe and 25% Ni exhibits >99% LA conversion with 98% selectivity to GVL within 1 h. IPA is found to be better solvent for levulinic acid (LA) to gamma-valerolactone (GVL) conversion, while substantial leaching of iron takes place when water is used as a solvent. It is observed that bimetallic sites are responsible for reduction of LA, while strong acidic sites of MMT are favoring subsequent cyclization to GVL. XPS analysis of fresh and reused Fe-Ni/MMT composites suggest that the catalyst surface does not undergo any chemical change during successive cycles, and the catalytic activity is retained up to six cycles. The plausible mechanism for LA to GVL conversion involves reductive cyclization processes through formation of levulinate ester that undergoes lactonization due to synergism in bimetallic nanoparticles and MMT clay.

Transfer hydrogenation of biomass-derived levulinic acid to gamma-valerolactone over supported Ni catalysts - Hengne, Amol M.; Kadu, Brijesh S.; Biradar, Narayan S.; Chikate, Rajeev C.; Rode, Chandrashekhar V. (RSC Advances, 2016)
A sustainable process of catalytic transfer hydrogenation (CTH) of levulinic acid (LA) to gamma-valerolactone (GVL) was investigated over Ni on various supports (Al2O3, ZnO, MMT and SiO2) in the presence of isopropanol (IPA) as the H-donor. Among these, the montmorillonite (MMT) supported Ni catalyst showed almost complete LA conversion (>99%) and selectivity (>99%) to GVL within 1 h. XRD and XPS results showed that the concentration of the metallic species significantly enhanced (two to four times) in the recovered sample as compared to the freshly prepared Ni/MMT. This was due to the in situ reduction of Ni2+ species present on the catalyst surface, through liberated H-2 under the reaction conditions. The strong acid strength of MMT, evidenced by NH3-TPD and py-IR, facilitated the esterification of LA as well as cyclization to GVL. The conversion-selectivity pattern was found to decrease in the IPA-water mixture while, it remained unchanged in the IPA-acetone mixture. Our catalyst could be efficiently recycled up to five times with consistent CTH activity and selectivity to GVL. The plausible mechanism of LA to GVL conversion involves the formation of a levulinate ester with IPA that favours its simultaneous hydrogenation and cyclization in a spontaneous manner to give GVL and regenerating IPA for sustainability.

MCM-41-supported phosphotungstic acid-catalyzed cleavage of C-O bond in allyl aryl ethers - Sakate, Sachin S.; Kamble, Sumit B.; Chikate, Rajeev C.; Rode, Chandrashekhar V. (New Journal of Chemistry, 2017)
Removal of the protecting allyl group from allyl aryl ethers in the presence of other oxygen protecting groups was successfully achieved using a solid acid supported on the high surface area material MCM-41. The catalyst showed excellent activity in the presence of various electron withdrawing, electron donating, and oxidizable functional groups. The methodology is also very useful for the removal of protecting allyl groups of various natural products such as vanillin, isovanillin, and other oxygen functionalized aldehydes and ketones.

Bifunctional role of Pd/MMT-K 10 catalyst in direct transformation of furfural to 1,2-pentanediol - Date, Nandan S.; Chikate, Rajeev C.; Roh, Hyun-Seog; Rode, Chandrashekhar V. (Catalysis Today, 2018)
The acid functionality of montmorillonite clay K 10 (MMT-K 10) was found to play a key role to give 1,2-pentanediol (1,2-PeDO) in Pd catalysed furfural hydrogenation. Among various Pd loadings on MMT-K 10, 3% Pd/MMT-K 10 catalyst exhibited excellent performance giving almost complete conversion of FFR and the highest selectivity of 66% to 1,2-PeDO. Py-IR of the catalyst evidenced the presence of Brønsted acidity which was responsible in C5-O cleavage of furan ring after the formation of furfuryl alcohol which is the first step intermediate in FFR hydrogenation. At a lower temperature of 140 °C, highest selectivity of 56% was achieved for FAL while increase in temperature to 220 °C, enhanced the selectivity to 1,2-PeDO. Keeping the temperature constant at 220 °C, with increase in H2 pressure from 500 to 750 psig, resulted in decrease in 1,2-PeDO selectivity from 66 to 34% with proportionate increase in THFAL selectivity. Thus as per the requirement, the product selectivities can be tailored by varying the reaction parameters suitably. Several control experiments were also performed the results of which combined with the characterization data allowed to propose a plausible reaction pathway for the formation of 1,2-PeDO.

Cascade synthesis of dihydrobenzofuran via claisen rearrangement of allyl aryl ethers using FeCl 3 /MCM-41 catalyst - Sakate, Sachin S.; Shinde, Suhas H.; Kasar, Gayatri B.; Chikate, Rajeev C.; Rode, Chandrashekhar V. (Journal of Saudi Chemical Society, 2018)
Dihydrobenzofuran as one of the active ingredients of the naturally occurring motif is synthesized by using in situ generation of ortho allyl phenols. Aryl allyl ethers on reacting with catalytic amounts of non noble metal iron (III) chloride supported on MCM-41 under moderate reaction conditions yield dihydrobenzofuran. First step via Claisen rearrangement gives ortho allyl phenol followed by its in situ cyclization to yield dihydrobenzofuran in very good yields. Both Lewis as well as Brønsted acidity of the catalyst as evidenced by Py-FTIR studies was found to catalyze the cascade synthesis of dihydrobenzofuran. The scope of the present strategy was successfully demonstrated for several substrates with varying electronic effects for the synthesis of corresponding dihydrobenzofuran with high yields in a range of 71-86%.
Keywords: Aryl allyl ether; Claisen rearrangement; Dihydrobenzofuran; Ferric chloride; MCM-41

Single pot selective hydrogenation of furfural to 2-methylfuran over carbon supported iridium catalysts - Date, Nandan S.; Hengne, Amol M.; Huang, K-W.; Chikate, Rajeev C.; Rode, Chandrashekhar V. (Green Chemistry, 2018)
Various iridium supported carbon catalysts were prepared and screened for the direct hydrogenation of furfural (FFR) to 2-methyl furan (2-MF). Amongst these, 5% Ir/C showed excellent results with complete FFR conversion and highest selectivity of 95% to 2-MF at a very low H-2 pressure of 100 psig. Metallic (Ir degrees) and oxide (IrO2) phases of Ir catalyzed the first step hydrogenation involving FFR to FAL and subsequent hydrogenation to 2-MF, respectively. This was confirmed by XPS analysis and some control experiments. At a low temperature of 140 degrees C, almost equal selectivities of FAL (42%) and 2-MF (43%) were observed, while the higher temperature (220 degrees C) favored selective hydrodeoxygenation. At optimized temperature, 2-MF was formed selectively while higher pressure and higher catalyst loading favored ring hydrogenation of furfural rather than side chain hydrogenation. With the combination of several control experimental results and detailed catalyst characterization, a plausible reaction pathway has been proposed for the selective formation of 2-MF. The selectivity to various other products in FFR hydrogenation can be manipulated by tailoring the reaction conditions over the same catalyst.

Single-pot reductive rearrangement of furfural to cyclopentanone over silica-supported Pd catalysts - Date, Nandan S.; Kondawar, Sharda E.; Chikate, Rajeev C.; Rode, Chandrashekhar V. (ACS Omega, 2018)
Direct one-pot hydrogenation of furfural (FFR) to cyclopentanone (CPO) was investigated over different silica-supported Pd catalysts. Among these, 4% Pd on fumed silica (4%Pd/f-SiO2) showed remarkable results, achieving almost 98% furfural (FFR) conversion with similar to 89% selectivity and 87% yield to cyclopentanone at 165 degrees C and 500 psig H-2 pressure. More interestingly, the fumed-silica-supported catalyst tuned the selectivity toward the rearrangement product, i.e, cyclopentanone, whereas all of the other supports were found to give ring hydrogenation as well as side chain hydrogenation products due to their parent Bronsted acidity and specific support properties. X-ray diffraction data revealed the presence of different phases of the face-centered cubic lattice of metallic Pd along with lowest crystallite size of 15.6 nm in the case of the silica-supported Pd catalyst. However, Pd particle size was found to be in the range of 5-13 nm with even dispersion over the silica support, confirmed by high-resolution transmission electron microscopy analysis. While studying the effect of reaction parameters, it was observed that lower temperature gave low furfural conversion of 58% with only 51% CPO selectivity.. Similarly, higher H-2 pressure lowered CPO selectivity with subsequent increase in 2-methyl furan and ring hydrogenation product 2-methyl furan and 2-methyl tetrahydrofuran. Thus, as per the requirement, the product selectivity can be tuned by varying the type of support and/or the reaction parameters suitably. With the help of several control experiments and the characterization data, a plausible reaction pathway was proposed for the selective formation of cyclopentanone.

One pot hydrogenation of furfural to 2-methyl tetrahydrofuran over supported mono- and Bi-metallic catalysts - Date, Nandan S.; Hengne, Amol M.; Huang, K. -W.; Chikate, Rajeev C.; Rode, Chandrashekhar V. (ChemistrySelect, 2020)
2-Methyltetrahydrofuran is a valuable commercial product that can be obtained by direct hydrogenation of furfural. In the present study, among several carbon supported bimetallic Ir-Ni catalysts with different loadings screened, 4% Ir-4% Ni/C catalyst showed excellent activity in terms of direct conversion (99%) to 2-MeTHF with a maximum selectivity of similar to 74% at 220 degrees C and 750 psig, suppressing the formation of side chain as well as ring opening products. The catalytic activity was found to be mainly affected by catalyst preparation methods, metal loadings, surface composition, temperature, pressure and catalyst loading. HR-TEM and STEM revealed well dispersed Ir-Ni NPs having the particle sizes in the range of 2 to 5 nm. Different phases of Ir i. e. Ir degrees and IrO(2)as well as oxygen vacancies were found to be responsible for hydrogenation of furfural to 2-methyl furan while, Ni degrees and NiO were responsible for further hydrogenation to 2-MeTHF. The synergic effect between Ir and Ni was established through XPS, H-2-TPR analysis. With the help of some control experiments, the plausible reaction pathway was also proposed. The catalyst prepared by co-impregnation method found more effective than prepared by sequential addition method. At lower Ni loadings of 1% and 2%, low temperature of 160 degrees C as well as at low H(2)pressure of 250 psig, mixture of furfuryl alcohol and 2-methyl furan were formed selectively. Catalyst could be successfully reused up to 3 times without leaching of metals.
Keywords: 2-Methyltetrahydrofuran; Bimetallic catalyst; furfural; Hydrogenation; OER type mechanism